A Distributed and Hybrid Ground Station Network for Low Earth Orbit Satellites - Vasisht, Deepak; Chandra, Ranveer (ACM HotNets, 2020)
Low Earth Orbit satellites for Earth observation have become very popular in recent years due to their ability to take high-resolution images of the Earth at high revisit rates. These satellites collect hundreds of Gigabytes of imagery during their orbit. This data needs to be downloaded using ground stations on Earth. However, due to the low altitudes, the satellites move fast with respect to a ground station on Earth, and consequently, have a few minutes time window to download the data to a single station. We propose a geographically distributed ground station design, DGS that improves robustness and reduces downlink latency. DGS is the first system to use a hybrid ground station model, where only a subset of ground stations are uplink-capable. This paper evaluates the feasibility of this design using simulations and empirical measurements.